Physical and methodological barriers in inclusive education - Muñoz Morán, Diana Marjorie; Vera Miranda, Lorena Yadira; Chuchuca Basantes, Iván (Revista Minerva, 2022)
This work presents results of the survey on barriers to learning and participation, used to build the baseline of the community care project Inclúyeme! Together we learn more, carried out by students of the sixth semesters of some careers of the Faculty of Philosophy, Letters and Education Sciences of the University of Guayaquil; applied in fiscal educational institutions and in a community center in the city of Guayaquil. The objective was to know the perception about the barriers to learning and participation from the experiences of authorities, teachers and parents with children who have some type of disability and how these affect the quality of life of Ecuadorian families. The applied methodology was descriptive and its main tool for data collection was the applied survey considering two types of barriers: infrastructure and methodological. The results obtained showed that the educational community is dissatisfied with the practice of half-inclusive education. There is still much to be done on inclusion issues, specifically with respect to the barriers investigated in terms of infrastructure and methodology in the classroom and family context.
Keywords: disability; perception; inclusion; NEE; caregivers